2018
DOI: 10.1080/16549716.2018.1451455
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of patient flow and provider efficiency of two delivery strategies for HPV-based cervical cancer screening in Western Kenya: a time and motion study

Abstract: Background: Improving patient flow and reducing over-crowding can improve quality, promptness of care, and patient satisfaction. Given low utilization of preventive care in low-resource countries, improved patient flows are especially important in these settings. Objective: Compare patient flow and provider efficiency between two cervical cancer screening strategies via self-collected human papillomavirus (HPV). Methods: We collected time and motion data for patients screened for cervical cancer in 12 communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…[13][14][15] The cost per woman screened across the six CHCs ranged from US $22.06 to $30.21 (Table 1). Detailed results comparing CHC screening and treatment costs and uptake are presented elsewhere, and showed the main driver of the difference in efficiency was personnel time in the health facilities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[13][14][15] The cost per woman screened across the six CHCs ranged from US $22.06 to $30.21 (Table 1). Detailed results comparing CHC screening and treatment costs and uptake are presented elsewhere, and showed the main driver of the difference in efficiency was personnel time in the health facilities.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed results comparing CHC screening and treatment costs and uptake are presented elsewhere, and showed the main driver of the difference in efficiency was personnel time in the health facilities. [13][14][15] The cost per woman screened across the six CHCs ranged from US $22.06 to $30.21 (Table 1). Most costs were fixed across CHCs, including tents, vehicles, data collection tools, and careHPV machine, so variations in costs and efficiency were mostly attributable to differences in personnel numbers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main uses of patient flow are for estimating wait time and visit time, 2,9,10 identifying bottlenecks in service providing processes, 11,12 optimizing schedules, 13,14 and planning for future reorganization and resource allocation. 8,[15][16][17] Studies have focused on a large variety of hospital departments, such as outpatient departments and clinics, emergency departments, inpatient wards, surgical units, and also diagnostic and paraclinic departments. 18 Results of studies have indicated that PFA was useful in controlling patient wait times and throughput in the system.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Recent studies address patient flow efficiencies within emergency departments. [3][4][5] It is difficult to find research on patient flow embedded in a large acute care hospital or integrated delivery system (IDS). In addition, the intra-hospital patient transport literature is focused primarily on ensuring the ergonomic safety of transport staff and wellbeing of transported patients.…”
Section: Introductionmentioning
confidence: 99%